Trade Policy Uncertainty and Inflation Nexus in China and Usa: Bootsrapt Rolling Window Approach - Türker Şimşek; Ayşenur Şakalak (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Two developed countries, namely China and the USA, which have been leaders in world trade in recent years, are making new trade regulations and increasing trade disputes, the intensity of political discourses, the effort to create new trade routes and thus decreasing the possibility of global trade integration, as a result, accumulating academic studies have focused on the study of trade policy uncertainty. For this purpose, in the study, the probable causality relationship between the trade policy uncertainty index and consumer price index data of China and the USA was tried to be determined by the Bootstrap Rolling Window Causality test developed by Balcılar et al. (2010). As a result of empirical studies, it was determined that there is a relationship between CPI and TPU variables in the long term in China and the United States. A one-way causal relationship has emerged from trade policy uncertainty in China to the Consumer Price Index; it has been concluded that there is a two-way causal relationship between trade policy uncertainty and inflation in the United States at certain dates. Considering the findings of the study in which the direction and dates of the causality relationship are determined, it is thought that the study will contribute to the relevant literature. At this point, the main purpose of future studies should be to clearly reveal the relationship between trade policy uncertainty and consumer price index with different econometric methods and examples from different countries.